Pluralisme Sosial Keagamaan Menuju Karakter Bangsa Yang Shalih - Zahratunnisa Hamdi (SALAM: Jurnal Sosial dan Budaya Syar-i, 2020)
The questioning argued that the social problems of the community were directed at the 2005 MUI fatwa which prohibits pluralism. MUI is seen as wrongly assessing the addition of the word "ism" as an ideological signification of the root word "plural", considering that the word pluralism in various linguistic and encyclopaedia literatures has more than just a theological meaning, but also a social meaning. However, critics have never provided a solution in the form of a substitute for the MUI version of pluralism. Besides, some of them are trapped in claiming to support the doctrine of equality of truth for all religions which is banned by MUI even though they try to appear objective at first. The method used in this research is qualitative research methods with a normative approach. The results of the research stated that MUI strives to fight for the harmony of Indonesia's pluralistic society through its formulated “plurality” inclusivism in the hope of realizing peace and harmony in a multi-religious nation. This paper also seeks several sides of the pluralism perspective in philosophical, religious and historical literature, and the possibility of applying its socio-political meaning in realizing the moral and righteous character of a national society.Keywords: Pluralism, Theology, Social Religion, Diversity AbstrakPenyoaalan berdalih persoalan sosial masyarakat diarahkan kepada fatwa MUI tahun 2005 yang mengharamkan faham pluralisme. MUI dipandang salah menilai tambahan kata “isme” sebagai penyifatan ideologis terhadap kata dasar “plural”, mengingat kata pluralisme dalam berbagai literatur kebahasaan dan ensiklopedi memiliki arti lebih dari sekedar makna teologis, tetapi juga makna sosial. Akan tetapi, para pengkritik tidak kunjung memberikan solusi berupa kata pengganti bagi pluralisme versi  MUI. Di samping, diantara merekapun terjebak untuk menyatakan mendukung doktrin persamaan kebenaran semua agama yang diharamkan MUI meskipun berusaha terlihat objektif di awal. Metode yang digunakan dalam penelitian ini adalah Metode Penelitian Kualitatif dengan pendekatan normatif. Hasil penelitian menyatakan bahwan MUI berupaya memperjuangkan harmoni masyarakat majemuk Indonesia melalui inklusivisme “pluralitas” yang dirumuskannya dengan harapan dapat mewujudkan kedamaian dan kerukunan bangsa yang multi agama. Tulisan ini pun mengupayakan beberapa sisi pandang pluralisme dalam literatur filsafat, agama dan kesejarahan, dan kemungkinan penerapan makna sosial politisnya dalam mewujudkan karakter masyarakat berbangsa yang bermoral dan shalih.Kata kunci: Pluralisme, Teologis, Sosial Agama, Keberagaman